2020
DOI: 10.2196/17770
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App to Manage Cirrhotic Ascites Among Outpatients: Feasibility Study

Abstract: Background Ascites is a common, painful, and serious complication of cirrhosis. Body weight is a reliable proxy for ascites volume; therefore, daily weight monitoring is recommended to optimize ascites management. Objective This study aims to evaluate the feasibility of a smartphone app in facilitating outpatient ascites management. Methods In this feasibility study, patients with cirrhotic ascites requiring… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…Another intensive outpatient monitoring program with a day hospital followed 80 patients with cirrhotic ascites and reduced early readmission by onethird (11.3% vs. 29.5%) [5]. Finally, a 25-patient pilot study of a remote weight monitoring program from our group found an 11% readmission rate for ascites, though a much higher rate for all-cause readmission [7]. We predict that a telemonitoring program specifically for patients undergoing ascites management, without day hospital or other ancillary supports, would likely fall somewhere between the outcomes of these four programs: increasing outpatient care utilization by approximately 15% and decreasing inpatient care utilization by approximately 15%.…”
Section: Telemonitoring Intervention Probabilitiesmentioning
confidence: 77%
See 2 more Smart Citations
“…Another intensive outpatient monitoring program with a day hospital followed 80 patients with cirrhotic ascites and reduced early readmission by onethird (11.3% vs. 29.5%) [5]. Finally, a 25-patient pilot study of a remote weight monitoring program from our group found an 11% readmission rate for ascites, though a much higher rate for all-cause readmission [7]. We predict that a telemonitoring program specifically for patients undergoing ascites management, without day hospital or other ancillary supports, would likely fall somewhere between the outcomes of these four programs: increasing outpatient care utilization by approximately 15% and decreasing inpatient care utilization by approximately 15%.…”
Section: Telemonitoring Intervention Probabilitiesmentioning
confidence: 77%
“…Two of the main reasons for readmission are failure to either arrange outpatient paracentesis for symptomatic ascites or recognize warning signs of over-diuresis [4]. Data are limited, however, supporting interventions that can reduce the burden of hospitalization for patients with ascites [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascites is a particularly common and costly cirrhosis complication that has been the target of several interventions aimed to reduce hospitalization frequency and length by improving timely access to paracentesis and redesigning acute models of care [4,5]. Though telemedicine and "automated hovering" interventions are particularly promising modalities that can improve access to care and inbetween visit monitoring, the evidence base for their clinical effectiveness and optimal implementation is still building for cirrhosis [6,7].In this issue of Digestive Diseases and Sciences, Bloom et al evaluated the costs and outcomes of a telemonitoring intervention for ascites in cirrhosis [8]. The authors developed a decision-analytic model that examined payerperspective costs of a standard-of-care compared with a telemonitoring intervention among 100 simulated patients at a tertiary care center over a 6-month horizon.…”
mentioning
confidence: 99%
“…Ascites is a particularly common and costly cirrhosis complication that has been the target of several interventions aimed to reduce hospitalization frequency and length by improving timely access to paracentesis and redesigning acute models of care [4,5]. Though telemedicine and "automated hovering" interventions are particularly promising modalities that can improve access to care and inbetween visit monitoring, the evidence base for their clinical effectiveness and optimal implementation is still building for cirrhosis [6,7].…”
mentioning
confidence: 99%